Ureteropelvic junction obstruction and renal cell carcinoma in a patient with solitary functioning kidney - Jeong, Young Beom; Ko, Oh Seok; Park, Hyung Sub; Cha, Jai Seong; Park, Seung Chol; Kim, Hyung Jin; Park, Jong Kwan; Shin, Yu Seob (Canadian Urological Association Journal, 2016)
We present a case of ureteropelvic junction obstruction (UPJO) and renal cell carcinoma (RCC) in a solitary functioning kidney (SFK), managed by robot-assisted dismembered pyeloplasty with partial nephrectomy in a single stage. To our best knowledge, we report the first case of UPJO with RCC in a congenital SFK.